Community profiling of water sources and uses in a rural setting in Northwest Province, South Africa - Xulu, Nqobile Thabisile (University of the Witwatersrand, Johannesburg, 2024)
Background Access to sustainable and potable water remains a constitutional right for all citizens regardless of their demographic, level of educational, or socioeconomic status. Rural communities are vulnerable to inadequate water supply and lack access to potable water, increasing their vulnerability to waterborne diseases and a lack of personal and environmental hygiene. The majority of residents in rural communities often resort to alternative water sources. Those water sources are often susceptible to contamination. The water contamination has been attributed to a lack of norms and monitoring plans aimed at protecting and preserving the quality of these water sources. Many studies have focused on identifying factors that influence water demand in urban and semi-urban areas to improve water resource planning and development. However, there have been limited studies focused on water use patterns and water profiling in rural areas, particularly where water is sourced from surface sources. Purpose The purpose of the study was to describe the socio-economic characteristics, water sources, water uses, and consumption patterns in Ganyesa village, Northwest Province. Methods A quantitative cross-sectional study design was employed to profile water sources and uses in a rural setting in the Northwest. A total of 175 households were randomly selected to participate in the study. A semi-structured questionnaire comprising of Section A: Household socio-economic data, Section B: Water sources, and Section C: Water consumption. Furthermore, water consumption daily activity diaries were used to collect information on water activity usage for seven (7) days. Results A total of 175 participants aged 18 to 65 years were included in this study. Most of the participants were females (78.28%, n = 137), and males accounted for (21.72%, n = 38). The majority of the study participants (37.17%, n = 65) were between the ages of 41 to 50 years, and the majority (58.5%) had a secondary education. v Participants use different water sources, such as communal taps, boreholes, bottled water, rainwater, water tankers, and rainwater, to meet their daily water needs. The water needs included activities such as bathing, cooking, and outdoor activities. Most of the participants (78,29%, n = 137) depend on communal taps as their primary water supply, followed by boreholes (19.4%, n = 34), and a small group of participants used both boreholes and communal taps (2.22%, n = 4). Participants used variety of alternative water sources to meet their daily water needs during water shortage from their primary water sources. Boreholes were the most used alternative water source (65,71% n=115), communal tap (20%, n=35), borehole and water tanker (7,43%, n=13), borehole and rainwater (2,86%, n=5), borehole and communal tap (2,29%, n=4). The average daily water consumption of one to three occupants was estimated to be 26.62 L/day per person. The average water consumption of males and females was estimated to be 29.6 L/day and 25 L/day, respectively. Several socio- demographic covariates were independently associated with water consumption. In terms of income, i.e., those earning R 5001-R 10000 per month had a statistically significant negative association with water consumption (p = 0.01), with a coefficient of -8.00. Similarly, the distance to the source of water was significant (p < 0.001), with a negative coefficient of -5.82, suggesting that as the distance from the water source increases, the average water consumption at the household level decreases. Gender disparity in water consumption was observed, male participants had a statistically significant reduction in water usage compared to their female counterparts (p = 0.02), with a coefficient of -3.84. Conclusion The study hypothesized that residents residing in rural settings use various water sources improved or unimproved to meet their water daily needs. Therefore, the hypothesis of this study is confirmed, meaning that rural dwellers of (Ganyesa) use both improved and unimproved water sources. Residents use both communal taps and boreholes as their primary water sources. The most used alternative source is borehole, indicating water unsustainability by Kagisano Molopo Local municipality. The alternative water sources used by residents are unimproved and unmonitored as per SANS 241. Groundwater was acknowledged as a remedy to water shortage. To prevent contamination to this groundwater sources the sustainability and preservation of this resource, effective management strategies and policies must be vi implemented. From the study, a conclusion can be made that most of the community members utilized communal taps for both indoor and outdoor activities. It was also found that water consumption at the household level is affected by various sociodemographic factors including household income, sex and distance to water source, the type of water source and number of occupants. This study provides scientific evidence that would help policy and decision makers to take these factors into consideration when addressing water scarcity and improving service delivery challenges to rural communities.
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine (Exposure Science) in Field Epidemiology, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; water sources; rural setting; Community profiling; water; household; accessible; potable; sufficient; SDG-3: Good health and well-being